2020
DOI: 10.1186/s12888-020-02828-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime co-occurring psychiatric disorders in newly diagnosed adults with attention deficit hyperactivity disorder (ADHD) or/and autism spectrum disorder (ASD)

Abstract: Background: Co-occurring psychiatric disorders in adults with Attention Deficit Hyperactivity Disorder (ADHD) and/ or Autism Spectrum Disorder (ASD) contribute to the burden of the healthcare and possibly to the delay of diagnosis. Aim of the study was to clinically assess the prevalence and compare lifetime co-occurring psychopathology in a sample of newly diagnosed ADHD and/or ASD adults and discuss the diagnostic challenges they pose. Methods: The lifetime prevalence rates of ten of the most frequently co-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 96 publications
1
34
1
Order By: Relevance
“…The present study was part of a larger research project on de novo diagnosed adults with ADHD and ASD [ 38 ]. The research group included 238 adults that were assessed at the Adult Neurodevelopmental Department in the 1st Department of Psychiatry at the National and Kapodistrian University of Athens and received a de novo ADHD and/or ASD diagnosis during a three-year period.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study was part of a larger research project on de novo diagnosed adults with ADHD and ASD [ 38 ]. The research group included 238 adults that were assessed at the Adult Neurodevelopmental Department in the 1st Department of Psychiatry at the National and Kapodistrian University of Athens and received a de novo ADHD and/or ASD diagnosis during a three-year period.…”
Section: Methodsmentioning
confidence: 99%
“…The Adult Neurodevelopmental Department is the only nationwide center that accepts referrals from the general population across Greece for the diagnosis of ASD and ADHD in adults. It used to be specialized for the diagnosis and treatment of adult ADHD [ 38 , 39 ], but during the last ten years, the increased needs for diagnosis and treatment of adults with ASD resulted in the broadening of referral criteria in order to include suspected ASD cases. The multidisciplinary team that carries out all assessments consists of psychiatrists who have extensive experience in the diagnosis and treatment of neurodevelopmental disorders in adults and are trained in Autism Diagnostic Observation Scale (ADOS) [ 40 , 41 ], Autism Diagnostic Interview –Revised (ADI-R) [ 42 , 43 ], and Diagnostic Interview for ADHD in Adults (DIVA) [ 3 , 5 , 44 ]; clinical psychologists; a speech and language therapist; an occupational therapist; a social worker.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been observed that some atypically developing individuals are close to the diagnostic threshold for ADHD and/or ASD, experience few behavioral problems, display good cognitive function, and perform well, while others demonstrate various psychiatric disorders. 6 In Japanese hospital pharmacists, ADHD and ASD traits have been reported to be associated with psychological distress, burnout, and compassion fatigue. 7 A major mission of medical education is to educate physicians to express compassion and empathy toward their patients.…”
Section: Introductionmentioning
confidence: 99%